Organized equity markets in Germany - Erik Theissen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
The German financial system is the archetype of a bank-dominated system. This implies that organized equity markets are, in some sense, underdeveloped. The purpose of this paper is, first, to describe the German equity markets and, second, to analyze whether it is underdeveloped in any meaningful sense. In the descriptive part we provide a detailed account of the microstructure of the German equity markets, putting special emphasis on recent developments. When comparing the German market with its peers, we find that it is indeed underdeveloped with respect to market capitalization. In terms of liquidity, on the other hand, the German equity market is not generally underdeveloped. It does, however, lack a liquid market for block trading.
urn:nbn:de:hebis:30-10227
Keywords: G21; 330; Market size; liquidity; floor versus screen trading